1996
DOI: 10.1897/1551-5028(1996)015<0670:popaco>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Polycyclic Aromatic Compounds of Different Molecular Size and Water Solubility in Surficial Sediment of an Intertidal Sandflat

Abstract: The persistence of 13 polycyclic aromatic hydrocarbons (PAHs), ranging from two-to six-ring compounds, in an intertidal sandflat was studied by applying uniform amounts (0.10 g) of each to the surface of the sandflat and then monitoring concentrations over time. The mass of total PAH, after initial losses, declined slowly, so that after 256 d 12% of the applied material remained. Vertical concentration profiles indicated that little downward movement occurred and that most of the mass was concentrated in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…The extend and the rate of dissipation of PAH compounds in the experiments of the present study was strongly related to hydrophobicity (log K ow ; Figure 4) reflecting the sorption affinity of these hydrocarbons to soil (Nam and Alexander, 1998;Harmsen, 2004). The usefulness of log K ow parameter to predict PAH persistence in soils was also pointed out in other studies (Maliszewska-Kordybach, 1993a;Krauss et al, 2000;Swerdrup, 2001), although other properties such as water solubility, molecular volume and molecular area were also considered to be useful (Wilcock et al, 1996;Maliszewska-Kordybach, 1998;Piatt and Brusseau, 1998). R 2 -determination coefficient adjusted for degrees of freedom (%); SOM -soil organic matter content (%); < 0.002 -fraction < 0.002 mm content (%); C ful -fulvic acid content (mg 100 g −1 ).…”
Section: Discussionsupporting
confidence: 74%
“…The extend and the rate of dissipation of PAH compounds in the experiments of the present study was strongly related to hydrophobicity (log K ow ; Figure 4) reflecting the sorption affinity of these hydrocarbons to soil (Nam and Alexander, 1998;Harmsen, 2004). The usefulness of log K ow parameter to predict PAH persistence in soils was also pointed out in other studies (Maliszewska-Kordybach, 1993a;Krauss et al, 2000;Swerdrup, 2001), although other properties such as water solubility, molecular volume and molecular area were also considered to be useful (Wilcock et al, 1996;Maliszewska-Kordybach, 1998;Piatt and Brusseau, 1998). R 2 -determination coefficient adjusted for degrees of freedom (%); SOM -soil organic matter content (%); < 0.002 -fraction < 0.002 mm content (%); C ful -fulvic acid content (mg 100 g −1 ).…”
Section: Discussionsupporting
confidence: 74%
“…In this sense, some correlations of sequestration extent and hydrophobic properties can be found in the literature. Wilcock et al [17] reported the feasibility of correlations between PAH persistence and properties such as molecular weight, molecular volume, etc. However, Kottler and Alexander [18] found no correlations at all between extractability with nbutanol and typical hydrophobic properties like K OW , molecular length, etc.…”
Section: The Sorption Stagementioning
confidence: 99%
“…PAHs tend to be considered persistent molecules, particularly those with a high molecular weight (HMW) (Cerniglia 1992; Wilcock et al. 1996) although recent conceptual models emphasise the importance of environmental parameters in controlling their persistence (Marín-Spiotta et al. 2014).…”
Section: Introductionmentioning
confidence: 99%